The Impact of Investment Horizon on the Return and Risk of Investments in Securities in Lithuania - Urbšienė, Laimutė; Bugajevas, Andrius; Pipiras, Marekas (Organizations and Markets in Emerging Economies, 2016)
The paper focuses on the impact of time horizon on risk and return, which usually is the object of discussions about “stock versus bond”. The aim of this paper is to investigate the transformation of risk and return when increasing the investment term, and to determine the impact of the investment horizon on investment results when investing in shares and bonds in Lithuania. The authors are proposing a hypothesis that a long-term investment in shares is not only more profitable, but also less risky than investment in bonds. Research of developed markets indicated that long-term investments in shares were more attractive than in bonds: the risk of shares fell to the risk of bonds, but at the same time, the return of shares remained high. However, there are just a few surveys in this field involving developing markets. Empirical results of this research are based on OMXV index and 10-year government bond data from Lithuania. Our results are different from the research results carried out by authors in developed countries and show that even with an increase in the investment horizon up to 60 months, the risk of shares in Lithuania still remains higher than the risk of bonds, and return of shares is lower than that of bonds. Risk premium for shares is negative during all the periods exceeding 12 months. The results suggest that investors with long-run investment horizons must consider the impact of horizon as well as the development of securities market they invest in.